Perceptions of alcohol use disorder support among liver transplant recipients: a survey of strategies and challenges - Cote, Maria P.; Rodríguez-Payan, Natalia; Atthota, Srilakshmi; Elias, Nahel; Dageforde, Leigh Anne (Frontiers in Transplantation, 2025)
BackgroundAlcohol use disorder (AUD) treatment in liver transplant (LT) recipients requires multidisciplinary management. We aim to analyze post-LT patients' perceptions of the transplant clinic, local community resources, desired supports and barriers for AUD recovery resources.MethodsA survey of adult recipients who received a LT within the last ten years with a history of AUD at a single Transplant Center was conducted. The survey consisted of five categories: demographics, strategies for AUD treatment used before and after LT, recent alcohol use, and challenges faced in AUD treatment. Results were reported using descriptive statistics.ResultsForty-one of 203 approached participants completed the questionnaire over a 3-month period [median age 56 years (45.5–62), 68.3% male, 90.2% white, median time since transplant 21 months (9.4–50.7)]. Thirty-three (80.5%) had a period of abstinence from alcohol prior to LT: 17 (41.5%) 1–5 years, 7 (17%) 6–12 months, and 7 (17%) < 6 months. 88.9% reported their goal for alcohol was complete abstinence. Useful strategies for AUD management before LT included exercise (73.1%), family support (63.4%), and therapy (58.5%). Exercise was most effective post-LT resource to prevent return to alcohol use, followed by social work assistance (51.2%), and finding a new hobby (48.8%). Social support and difficulties with availability of AUD treatment resources were the main challenges perceived by survey participants.ConclusionExercise, social support, social work assistance, finding new hobbies, and therapy were the preferred resources for AUD management. Future interventions should facilitate access to resources to assist with sobriety and incorporate their outside support network in assisting with recovery from AUD.